Management and cultivar effects on ruminant nutritional quality of pearl millet (Pennisetum glaucum (L.) R. Br.) stover. II. Effects of cultivar choice on stover quality and productivity - Blümmel, Michael; Bidinger, F.R.; Hash, C.T. (Elsevier, 2007)
The paper investigates the variation in laboratory fodder quality traits in stover of 16 cultivars of pearl millet grown over 2 consecutive years and subjected to two different fertilizer regimes and planting densities. Stover quality traits were nitrogen and sugar content, in vitro digestibility and metabolizable energy content as well as yield of digestible and metabolizable stover. Significant (P < 0.05) cultivar-dependent variations were observed for all these quality traits. Stover nitrogen contents were mostly below the levels (1.2% of dry matter) considered to be the minimum required for efficient feed digestion in the rumen, but choice of cultivar plus nitrogen fertilizer application could raise nitrogen levels to near, equal or above this threshold. Stover sugar contents were below 5% and mostly concentrated in the stems. Across management regimes stover in vitro digestibility varied by about 4% units, and by about 3-5% units within individual management regimes. Stover metabolizable energy contents of cultivars varied such that stover from superior cultivars could provide the energy maintenance requirement of livestock and theoretically moderate levels of live weight gains, while livestock fed on stover from poor cultivars would lose live weight. Yields of digestible and metabolizable stover (yield of stover dry matter times stover in vitro digestibility/metabolizable energy) varied among cultivars by at least 1.7-fold. Stover quality traits and grain yields of cultivars were largely unrelated (P > 0.05) suggesting that high stover quality will not be achieved on the expense of grain yield. Heritabilities for stover quality traits were high (h2 > 0.73) except for stover nitrogen content (h2 > 0.56).